Ekofeminisme dan Peran Perempuan Indonesia Dalam Perlindungan Lingkungan - EraPurike EraPurike; Fitriani Tobing; Nur Azizah; Priatna Kesumah (Lembaga Pengembangan Kinerja Dosen, 2023)
Ecological feminism is feminism that seeks to unite the demands of the women's movement with the ecological movement to realize a world and worldview that is not based on the domination of socio-economic and conceptual structures. Ecofeminism challenges the dominant paradigm that has perpetuated the oppression of women and the degradation of nature. Women's roles in both the domestic and public spheres intersect with the environment. Hence, of course, it can have positive and harmful environmental effects. This research uses a literature study method where several studies are related to the main principles of ecofeminism, historical development, and contributions to environmental discourse. This research reveals that women in various regions of Indonesia still need to be included in environmental management in terms of access, participation, control, and benefits. Thus, ecofeminism advocates for social and ecological justice, aiming for a more just and sustainable future for all. It concludes that women and men have equal roles in maintaining the environment for a sustainable life.